A relação trabalho e saúde de coletores de lixo domiciliar - Souza, Celiana Pereira de (2018)
The purpose of this dissertation is to analyze the relationship work and health of household garbage collectors middle-sized city of the Brazilian Northeast. From a theoretical point of view, the ergonomics of the activity and the work psychodynamics are the approaches used to analyze the relationship between work and health that emerged in this study. As for the method, favored a qualitative approach that had as instruments A semi-structured individual interviews and a sociodemographic questionnaire. For the analysis of the data, we opted for the analysis of thematic content from the perspective of Laville and Dione. A total of 13 male household waste collectors, aged 25 to 51 years (M = 32, DP = 6.94) participated in this study. The results are presented in three articles. In the first, it was verified that the work trajectory of these workers is similar, signaled by informal jobs, without guaranteed fixed salary and basic rights, won only when they became collectors. On the other hand, it was detected that the collectors work without any professional training, which makes them even more vulnerable to this precarious, risky and unhealthy activity. In the second, it was shown that the collectors are exposed to a diversity of risks (physical, chemical, biological, ergonomic, mechanical and social) and that this exposure carries different health consequences. It was also identified that the relation of the collectors with the risks is mediated by the use of defensive strategies capable of mitigating them, however, that little collaborate to positively transform the real situations of risks. In the third, the lack of recognition by the hierarchy (directors, bosses, supervisors) was evidenced, and although the collectors receive recognition from the clients / users, the relation with the latter is not without constraints and displeasures. Finally, collectors find in their peers the most abundant source of recognition for the activity they do.